Adsorption method using zeolite to produce fuel grade bioethanol - Hargono Hargono; Noer Abyor Handayani; Sheila Dwifa Andani; Ersa Wardani; Ulma Aqari Fisama; Kevin Setiadi Seng (International Journal of Renewable Energy Development, 2023)
Bitter cassava (Manihot glaziovii) has the potential to be converted into bioethanol. However, the distillation process can only purify it to 95% bioethanol. Therefore, it is necessary to carry out an adsorption process to obtain 99.8% bioethanol. This study aimed to investigate the effect of bitter cassava starch hydrolysis time and coral rock in the distillation column on glucose and bioethanol concentrations, respectively. Additionally, the study discussed the effect of adsorbent height (60, 80, 100, or 120 cm) in the adsorption column on bioethanol concentration. There are three main stages for obtaining fuel-grade bioethanol: (i) bitter cassava hydrolysis, (ii) bioethanol production, and (iii) bioethanol purification (distillation and adsorption). Zeolite 4A and natural zeolite were used as adsorbents in this study. The results showed that the best fermentation was obtained at 90 hours, resulting in an ethanol concentration of 13.82% (v/v), which could be purified up to 95.64% through distillation. Furthermore, further purification (adsorption) could extend fuel-grade bioethanol (99.62% and 98.42%). Another analysis also indicated that zeolite 4A was more feasible than natural zeolite for producing fuel-grade bioethanol.